METHOD OF PORTOFOLIO RESUME ASSIGNMENT TO IMPROVING STUDENTS CONCEPT COMPREHENSION TOWARDS MOLECULAR CELLULAR BIOLOGY CLASS - Rizkia Suciati; Suci Lestari (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
METODE PENUGASAN RESUME PORTOFOLIO UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA DALAM MATAKULIAH BIOLOGI SEL MOLEKULER Abstract Cell and molecular biology are among the topics that have led to the application of molecular technology. Problems arise when learners lack understanding of concepts or even frequent misconceptions due to many abstract concepts. This study aims to determine the level of student understanding through a resume in the form of a portfolio. The research method used descriptive approach. The population of the study is the students of Biology Education study program which has taken the subject of cell Biology and molecular number of 102 students, and the sample determination using random cluster so that 40 students are obtained. Data were analyzed descriptively-quantitative. Based on the findings in the field, it is known that the average value of the resume portfolio of 71.60 and categorized high. Thus, the students' concept of understanding is in the high category so that the assignment method makes the resume in the form of portfolio able to give better understanding of the concept of lecture material of Cell and Molecular Biology, with the average value of concept understanding through portfolio is in high category. Abstrak Biologi sel dan molekuler merupakan salah satu topik yang sudah mengarah pada penerapan teknologi molekuler. Permasalahan muncul ketika peserta didik kurang memahami konsep atau bahkan sering miskonsepsi karena banyak konsep yang bersifat abstrak. Penelitian ini bertujuan untuk mengetahui tingkat pemahaman mahasiswa melalui resume dalam bentuk portofolio. Metode penelitian menggunakan pendekatan deskriptif. Populasi penelitian adalah mahasiswa program studi Pendidikan Biologi yang telah mengambil matakuliah Biologi sel dan molekuler berjumlah 102 orang, dan penentuan sampel menggunakan cluster random sehingga diperoleh 40 mahasiswa. Data dianalisis secara deskriptif-kuantitatif. Berdasarkan hasil temuan di lapangan, diketahui bahwa nilai rata-rata hasil resume portofolio sebesar 71,60 dan dikategorikan tinggi. Dengan demikian, pemahaman konsep mahasiswa berada dalam kategori tinggi sehingga metode penugasan membuat resume yang berupa portofolio mampu memberikan hasil pemahaman konsep materi perkuliahan Biologi Sel dan Molekuler menjadi lebih baik, dengan nilai rata-rata pemahaman konsep melalui portofolio berada dalam kategori tinggi. Permalink/DOI:http://dx.doi.org/10.15408/es.v10i1.7243